Complexity Rising: From Human Beings to Human Civilization, a Complexi ty Profile - Bar-Yam, Yaneer (New England Complex Systems Institute, 1997)
It is generally recognized that life is becoming more complex. This ar ticle analyzes the human social environment using the "complexity prof ile," a mathematical tool for characterizing the collective behavior o f a system. The analysis is used to justify the qualitative observatio n that complexity of existence has increased and is increasing. The in crease in complexity is directly related to sweeping changes in the st ructure and dynamics of human civilization—the increasing interdepende nce of the global economic and social system, and the instabilities of dictatorships, communism and corporate hierarchies. Our complex socia l environment is consistent with identifying global human civilization as an organism capable of complex behavior that protects its componen ts (us) and which should be capable of responding effectively to compl ex environmental demands.